Morphometry of Limulidae (Oscar E. Brown) in Leidong, Sei Berombang, and Tanjung Tiram, North Sumatera - Zhulian Hikmah Hasibuan; Ita Widowati; Ervia Yudiati; Syukur Syukur (Marine Science Department Diponegoro University, 2023)
Limulidae (Horseshoe crab), or Mimi in the local name, are known; there are four species, namely Limulus polyphemus in North America and Asia, namely Tachypleus tridentatus, T. gigas, and Carcinoscorpius rotundicauda. In Indonesia, these species are protected by the Decree of the Minister of Forestry Number 12/KPTS-II/1987; meanwhile, illegal fishing still occurs. This study aims to identify Limulidae species and analyze Mimi's morphometric characteristics and distribution in North Sumatra to conserve the species. This research was conducted using a quantitative descriptive method in Leidong, Sei Berombang, Tanjung Tiram - North Sumatera, from September to December 2021. Biometric measurements were performed on 98 Mimi, and the data were statistically analyzed using the Kruskal Wallis test, Mann-Whitney test, and Multinomial logistics. The results showed that Mimi in the study area was identified as Tachypleus tridentatus, T. gigas, and Carcinoscorpius rotundicauda. The most commonly caught was T. tridentatus at the Tanjung Tiram. Based on the maximum width of the prosoma and body length, the largest to most petite sizes are T. tridentatus at Leidong (10.31 cm), T. gigas at Leidong, and Sei Berombang (10 cm) and C. rotundicauda at Sei Berombang (7.56 cm) respectively. The cluster analysis based on 27 morphometric characters showed that T. tridentatus had almost the same characteristics as T. gigas, while C. rotundicauda had its features. It can be concluded that the largest to most petite sizes of Mimi in the study area were T. tridentatus, T. gigas, and C. rotundicauda, respectively.